Academic improvement through participation in the tutorial education program - Hemsing, Daniela (2022)
As a result of the rapid process of changes in all areas that the human being is inserted, there has been an increasing search for improvement in the teaching environment, in which the student stops being a mere listener and enters the scene applying the theory in practice. In this way, the Tutorial Education Program (PET) emerges as a tool that uses the teaching, research and extension triad as a way to bring the university closer to society through the performance of its actions. The PET Veterinary Medicine / Family Agriculture of the Federal University of Fronteira Sul was created in 2010, at the same time as the implementation of the veterinary medicine course at the institution. Due to the large number of small properties of dairy cattle farming, it was necessary to provide assistance to the properties, providing information, technical and practical knowledge that would contribute to improving the quality of the milk produced. The objective of this report is to address the role of extension activities developed in the professional and personal training of program graduates. The testimonies of 20 students and two tutors were analyzed, as well as information in reports, plans, action plans of the most diverse activities developed by the program during the same period, in addition to data from the lattes curriculum of each graduate. The reports differently highlight the importance of participating in the program, with emphasis on outreach and social activities. The graduates enjoyed the possibility of training with a differential, which made them more qualified to exercise the profession, with responsibility and ethics, in addition to contributing to the development of society and the permanence of farmers in the field.